Electrical characterization of commercial NPN bipolar junction transistors under neutron and gamma irradiation - Oo, Myo Min; Alang Md Rashid, Nahrul Khair; Abdul Karim, Julia; Mohamed Zin, Muhammad Rawi; Ab Rahim, Rosminazuin; Azman, Amelia Wong; Hasbullah, Nurul Fadzlin (2014)
Electronics components such as bipolar junction transistors, diodes, etc. which are used in deep space mission are required to be tolerant to extensive exposure to energetic neutrons and ionizing radiation. This paper examines neutron radia tion with pneumatic transfer system of TRIGA Mark-II reactor at the Malaysian Nuclear Agency. The effects of the gamma radiation from Co-60 on silicon NPN bipolar junction transistors is also be examined. Analyses on irra-diated transistors were performed in terms of the electrical characteristics such as current gain, collector current and base current. Experimental results showed that the current gain on the devices degraded significantly after neutron and gamma radiations. Neutron radiation can cause displacement dam age in the bulk layer of the transistor structure and gamma radia -tion can induce ionizing damage in the oxide layer of emit ter-base depletion layer. The cur rent gain degradation is believed to be governed by the in creasing re combination current in the base-emitter depletion region.